Regional Economic Outlook, April 2021, Sub-Saharan Africa. (International Monetary Fund, 2021)
Sub-Saharan Africa is still contending with an unprecedented health and economic crisis. In the months since the October 2020 Regional Economic Outlook: Sub-Saharan Africa, the region has confronted a second coronavirus (COVID-19) wave that swiftly outpaced the scale and speed of the first. While this episode has eased for now, many countries are bracing for further waves, particularly as access to vaccines remains scant.